Kekerasan Dalam Rumah Tangga (KDRT) Perspektif Undang-Undang Nomor 23 Tahun 2004 dan Hukum Islam - A. Malthuf Siroj (JURNAL HAKAM, 2020)
Cases of domestic violence often occur in society and has become a very complex social problem. From year to year this case rapidly growing both quantitatively and qualitatively. Because of that,  Act No. 23 of 2004 comes to resolving  the cases of domestic violence , in addition to other laws related. Domestic violence includes any act that causes misery and suffering due mainly to women's physical, psychological, sexual or neglect of household. But according to Islamic law, wife beating because of nusyuz or children who were aged 10 years and still leave the obligatory prayers is not included in the category of domestic violence because this kind of action aimed educative. The domestic violence according to the school of Bio-sociological (school of Convergence) occurs due to internal factors (innate character, psychological) and external factors (environmental sociological) that encourage acts of violence. According to Islam, a violent action is mainly due to the weakness of the practice of religious values in family life, because in principle the humankinds were  born early  in a state of purity and after that their personality is determined by the mode of education and the dynamics of the environment surrounding them. To cope with domestic violence do efforts pre-emptive, preventive and repressive. The repressive effort was the last attempt to do after other efforts did not succeed. According to Islamic law when there has been a sign of disharmony (syiqaq) between the spouses, the settlement must be internally first by involving two mediators (hakamain) of each family of husband and wife. If this kind of settlement efforts are not successful then the solution that can be taken is talaq (divorce) to avoid more fatal  consequences. For the perpetrators of domestic violence Act No. 23 of 2004 provides a penalty of imprisonment or fines and additional penalty, while according to Islamic law, these violent acts, including category jarimah qisas-diyat or ta'zir depending on mode of action and the consequences thereof. Keywords: Violence, Domestic, Act No. 23 of 2004, Islamic Law.